Predicting mortality in heart failure: BUN/creatinine ratio in MIMIC-III - Zhu, Changsen; Wu, Liyan; Xu, Yiyi; Zhang, Qian; Liu, Wenbo; Zhao, Yuxiang; Lyu, Jun; Chen, Zhuoming (Frontiers in Cardiovascular Medicine, 2025)
AimsHeart failure is a critical health issue with high mortality rates. The blood urea nitrogen/creatinine ratio (BCR) has proven more effective at predicting outcomes in heart failure patients than individual assessments of each marker. Nevertheless, the implications of varying BCR levels for outcomes among heart failure patients remain to be fully understood. This study explores the impact of BCR on the outcomes of these patients.Methods and resultsEmploying a retrospective cohort design at a single center, this study examined 1,475 heart failure patients from the Medical Information Mart for Intensive Care (MIMIC-III) database, categorized into four quartiles based on their BCR levels. We analyzed survival outcomes using Kaplan–Meier and Cox proportional hazards models, supplemented by restricted cubic splines to elucidate detailed associations. The average age of the patients was 69.52 years, with males constituting 55.6% of the cohort. As BCR values escalated, the average hospital stay increased from 9.64 to 14.15 days, and average survival decreased from 685.11 to 412.68 days. Patients in the highest BCR quartile faced the most severe mortality rates, with 18.8% in-hospital and 78.3% long-term mortality. Nonlinear regression revealed a U-shaped relationship between BCR and mortality: at BCR levels below 12.5, there was no significant correlation with long-term mortality; between 12.5 and 22, BCR appeared to exert a protective effect; and above 22, it emerged as a significant risk factor.ConclusionsAdmission BCR values are non-linearly associated with mortality in heart failure patients, suggesting its utility as a prognostic tool in critical care.